2015
DOI: 10.1002/2015wr016943
|View full text |Cite
|
Sign up to set email alerts
|

Water conservation and hydrological transitions in cities in the United States

Abstract: Cities across the world have had to diversify and expand their water supply systems in response to demand growth, groundwater depletion and pollution, and instability and inadequacy of regional surface freshwater sources. In the U.S., these problems plague not only the arid Western cities but increasingly also cities in the Eastern portions of the country. Although cities continue to seek out new sources of water via Promethean projects of long-distance supply systems, desalinization plants, and the recharge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…These findings are also consistent with the analysis by Hornberger et al . [] who found higher AWE conservation scores aligned with low electricity use, high gross state product (i.e., rich states), and high surface water use per capita tend to have the higher AWE scores.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are also consistent with the analysis by Hornberger et al . [] who found higher AWE conservation scores aligned with low electricity use, high gross state product (i.e., rich states), and high surface water use per capita tend to have the higher AWE scores.…”
Section: Resultsmentioning
confidence: 99%
“…Hornberger et al . () analyzed self‐reported conservation in the 2010 AWWA survey and showed that cities tend to be conservation adopters if they have a high median household income, a high system development charge, and a high fee for residential customers who use over 3,000 cubic feet of water per month.…”
Section: Introductionmentioning
confidence: 97%
“…Other options include large-N statistical studies (e.g. Hornberger et al, 2015), which seem very promising for comparative socio-hydrology, and survey research, for instance on how farmers actually react to hydrological change (Sanderson and Curtis, 2016) or on what actually determines environmental concern: personal characteristics or local environmental problems (Hannibal et al, 2016). The reason why this article focused on qualitative case study research and coupled modelling is that coupled modelling is the most popular approach in socio-hydrology and qualitative case study research is a contrasting approach with many potential benefits.…”
Section: Discussionmentioning
confidence: 99%